Factores para el uso intensivo del automóvil en las urbes mexicanas. Entre las variables socioeconómicas y las actitudes hacia la movilidad sustentable - Calonge-Reillo, Fernando (2024)
Despite the numerous efforts made to reduce the use of automobiles as a daily mode of transportation, their presence continues to increase in certain contexts like Latin America. The objective of this article is to examine some factors that explain the intensive use of cars in Mexico's large cities. The study is based on a statistical analysis of the Household and Environment Module and the National Household Survey conducted by the National Institute of Statistics and Geography (Mexico). The findings reveal that the possession of mobility resources, such as cars, plays a significant role in explaining the number of vehicles used weekly, and that socioeconomic variables such as educational level or socioeconomic status are also key. However, it is noted that favorable attitudes toward sustainable mobility or the perception of the adverse effects of climate change lead to a reduction in gasoline consumption, and that these factors are independent of socioeconomic ones. The article leaves open the possibility that, as environmental concerns increase, these attitudinal and perception variables could offset the strong influence of socioeconomic factors on the intensity of car use.